Living the work promoting social justice and equity work in schools around the world - Boske, Christa; Osanloo, Azadeh F. (Bingley, U.K. : Emerald, 2015)
This unique volume has been written collaboratively by children, families, teachers, school leaders, scholars, and community organization representatives. With each author having a platform to express his or her individual voice, chapters center on the authors' lived experiences (ranging in skills, knowledge, and activism) in promoting social justice and equity in schools. With a focus on long-standing trends in schools regarding ability (both mental and physical), race, ethnicity, class, religion/beliefs/faith, native language, immigration status, gender, sexuality, family structure, and geographical location, the authors demonstrate how they live their work by facilitating courageous dialogue, promoting inclusive practices, and building authentic relationships with those in power as well as those from marginalized populations. Authors reflect on their personal and professional lives and help the reader understand the call that lies within each of them: to live what is just and right for all children.
My rules of engagement / Sander Capetz -- Teaching students to fish : advancing social justice and equity pedagogy and praxis through scholarship and instruction / Cosette M. Grant -- Radical loving, radical leading : negotiating complex identities, positionalities and pedagogies in social justice work / Ty-Ron M.O. Douglas, Christine W. Nganga -- Promoting inclusive practices : using art and inquiry to promote social justice in schools / Barbara S. Hawley -- One teacher's journey to create change / Kimberly A. Kohut -- Building a rainbow, one writer at a time : an urban youth memoir project / Darolyn "Lyn" Jones -- I live my work by being out / Angely Boske -- The evolution of my voice / AmariYah S. Israel -- Building awareness of race and place : reflections from a multiracial research group on impactful life experiences / Amy P. Lippa ... [et al.] -- Hear our words; honor our heritage : decolonizing pedagogy in the urban classroom / Marva McClean -- Addressing the education debt owed to students in an urban environment through a school and community collective impact model of collaboration / Joseph John Morgan -- An asking year / Nicole Thomas -- Dare greatly to enhance your schools climate; through acceptance, relational trust, and creating a sense of belonging / Ryan S. Schoenfeld, Jeff Dinse -- Utilizing student voices to enhance academic resilience in Kenya / Teresa A. Fisher, Teresa A. Wasonga, Grace Wambu -- Creating achievement opportunities : each one reach one / Kershini Naidu -- Improving psychological wellbeing of children : a social justice journey in the borderlands / Ivelisse Torres-Fernandez -- An investigation of how historically marginalized third graders manifest criticality and resistance in school / Marisol Moreno, H. Prentice Baptiste -- Dig it! The versatility of the community garden / Melinda VanDevelder, Kierstyn Johnson, Alicia R. Thompson -- Becoming and staying an ally / Alana Jochum -- Being a champion / Sahadeo Ramharrack -- My journey / Noldon Starks -- Leadership as soul work : living, leading, and loving the work / Judy A. Alston -- Conclusion : preparing all school community leaders to live their work / Christa Boske, Azadeh F. Osanloo.
Print version record
Keywords: Education -- Educational Policy & Reform -- General; Education; Social justice -- Study and teaching; Educational equalization